Analisis Efektivitas dan Efisiensi Pajak Reklame Serta Prospeknya di Kabupaten Badung - Kusuma Arsana A.B, I Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 4, April 2013 (pp. 173-225), 2013)
Government expected can improve Original Earnings of Area ( PAD) by maximizing available area potency. Area also have to ready for arranging available resource and management with as efficient as and as effective as possible. Iease one of the source of Original Earnings of Area ( PAD) which have potency to be improved to the fore is effectively. Effectiveness in acceptance of tired by area Iease if abysmal realization of goals which wish to be reached. Therefore the source of Original Earnings of Area ( PAD) had to need allocation or exploited can be collected chronically. Target of this research is, To know effectiveness storey;level and efficiency and also advertisement Iease prospect in Sub-Province Badung to in future. Result of analysis from this research indicate that, Effectiveness storey;level acceptance of advertisement Iease in Sub-Province Badung pertained is effective. Efficiency storey;level acceptance of advertisement Iease in Sub-Province Badung pertained is efficient. While prospect acceptance of advertisement Iease in Sub-Province Badung admit of to be improved with approach action and observation.
Keywords: advertisement Lease , efficiency , effectiveness